Prevalence and correlates of dyslipidemia in HIV positive and negative adults in Western Kenya: A cross-sectional study. Issue 10 (12th March 2021) - Tilahun, Hailu; Masyuko, Sarah J.; Mogaka, Jerusha N.; Temu, Tecla; Kinuthia, John; Osoti, Alfred O.; Nakanjako, Damalie; Farquhar, Carey; Page, Stephanie T.
Abstract : Abstract: There is increasing morbidity and mortality from cardiovascular diseases (CVD) in sub-Saharan Africa (SSA). Dyslipidemia is a well-known CVD risk factor which has been associated with human immunodeficiency virus (HIV) infection and its treatment in high-income countries. Studies in SSA that have examined the relationship between HIV and dyslipidemia have reported mixed results. In this study, we sought to determine the prevalence of dyslipidemia in HIV positive and negative adults (>=30 years old) and evaluate for association in Western Kenya with a higher prevalence expected among HIV positive individuals. HIV positive adults receiving antiretroviral therapy (ART) and HIV negative individuals seeking HIV testing and counseling services were recruited into a cross-sectional study. Demographic and behavioral data and fasting blood samples were collected. Dyslipidemia was defined according to the National Cholesterol Education Program Adult Treatment Panel III. Associations between baseline demographic and clinical variables and dyslipidemia were analyzed using logistic regression. A total of 598 participants, 300 HIV positive and 298 HIV negative adults were enrolled. Dyslipidemia data was available for 564 (94%) participants. In total, 267 (47%) had dyslipidemia. This was not significantly different between HIV positive and HIV negative individuals (46% vs 49%, P = .4). In a multivariate analysis including both HIV positive and negative individuals, adults 50 to 59 years of age had a 2-fold increased risk of dyslipidemia (Odds ratio [OR] 2.1, 95% confidence interval (1.2–3.5) when compared to 30 to 39-years-old participants. Abdominal obesity (OR 2.5), being overweight (OR 1.9), and low fruit and vegetable intake (OR 2.2) were significantly associated with dyslipidemia. Among HIV positive participants, time since HIV diagnosis, ART duration, use of (PI) protease inhibitor-based ART, viral load suppression, current cluster of differentiation (CD4) count and nadir CD4 did not have significant associations with dyslipidemia. The prevalence of dyslipidemia is high in Western Kenya, with nearly half of all participants with lipid abnormalities. Dyslipidemia was not significantly associated with HIV status, or with HIV-specific factors. Older age, being overweight, abdominal obesity, and low fruit and vegetable intake were associated with dyslipidemia and may be targets for public health interventions to lower the prevalence of dyslipidemia and CVD risk in sub-Saharan Africa.